2015
DOI: 10.1016/j.jegh.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Extracurricular activities associated with stress and burnout in preclinical medical students

Abstract: This study aims to assess the prevalence of stress and burnout among preclinical medical students in a private university in Beirut, Lebanon, and evaluate the association between extracurricular involvement and stress and burnout relief in preclinical medical students. A cross-sectional survey was conducted on a random sample of 165 preclinical medical students. Distress level was measured using the 12-item General Health Questionnaire (GHQ-12) while that of burnout was measured through the Maslach Burnout Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
174
4
55

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(251 citation statements)
references
References 36 publications
18
174
4
55
Order By: Relevance
“…Students reporting lower levels of academic satisfaction presented higher burnout, supporting the hypothesis that students' depersonalization may be a possible explanation for lower academic satisfaction 78 which can undermine students' satisfaction and accomplishments in their future professional lives. 79,80 Psychological interventions focused on reducing burnout symptoms in pharmacy school, previously used to manage students' psychological distress and lack of academic motivation, 41,81,82 could have beneficial results in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students reporting lower levels of academic satisfaction presented higher burnout, supporting the hypothesis that students' depersonalization may be a possible explanation for lower academic satisfaction 78 which can undermine students' satisfaction and accomplishments in their future professional lives. 79,80 Psychological interventions focused on reducing burnout symptoms in pharmacy school, previously used to manage students' psychological distress and lack of academic motivation, 41,81,82 could have beneficial results in our population.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] However, some authors have reported that the ability to take patients' perspectives and to act compassionately, enhances professional accomplishment, thereby reducing depersonalization. 39,40 High burnout levels among medical, 41 dental, 42 pharmacy, 43 and nursing students 44 may be a consequence of dealing with academic stress, 25,33 social and family demands, 43 and exposure to emotional suffering. 45 High levels of stress during school years, leading to student's' burnout, are related to intrinsic and contextual variables.…”
Section: Introductionmentioning
confidence: 99%
“…15 From the preclinical years through the clinical years, the level of support provided by faculty, and the workload and facts to be learned within a limited time were found to be associated with student burnout. 16,17 Given that promotion of involvement in the first year of medical school is an essential method of establishing bases for success in subsequent years, 18 problems with medical students' mental health should be addressed from the very start of the degree program. In this study, we focus on the transition from secondary to medical school.…”
Section: Introductionmentioning
confidence: 99%
“…During student life, such distress can lead not only to sleep http://dx.doi.org/10.15405/epsbs.2017.05.02.199 Corresponding Author: Luminita Georgescu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 1624 difficulties, but also to mood changes, frustration, depression, memory dysfunctions, and decreased academic performance, low self-esteem and poor quality of life (Gaultney, 2010;Pagnin & De Queiroz, 2015;Fares et al, 2016).…”
Section: Theoretical Foundation and Related Literaturementioning
confidence: 99%